Design and Implementation of a Music Bot and Its Impact on the Community of the Discord Server Slowly - Hariadi, Fadli; Husain, Husain; Hammad, Rifqi (Yayasan Bina Internusa Mabarindo, 2025)
This study aims to design, implement, and evaluate a music bot integrated into the Discord platform, as well as to analyze its impact on community interactions within the “Slowly” Discord server. The bot was developed using the Python programming language and the discord.py library, and tested through black-box testing to ensure the reliability of its core features such as play, pause, resume, skip, queue, and disconnect. The findings indicate that the bot operates stably and meets user expectations. In terms of usage, the bot contributes to increased interaction within the community. The average number of users in the voice channel increased from 1–3 to 4–7 users per day, while the average session duration grew from 2–3 hours to 3–5 hours. Furthermore, during one week of observation, a total of 58 songs were played, demonstrating that the bot not only serves as an entertainment tool but also strengthens social engagement within the community. This study recommends further development including the addition of comprehensive documentation (help command), performance optimization to reduce delays, periodic evaluation of user needs, and migration to cloud hosting services to ensure system availability. Thus, the Discord music bot has the potential to become an integral part of enhancing social interaction and user experience in online communities